High-purity and high-stability nickel-based single crystal superalloy and preparation method thereof
Patent Information
- Application Number
- CN202611258872.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-19
AI Technical Summary
(1)本发明通过合理调控强化元素与基体元素的含量范围,在保证固溶强化和γ′相沉淀强化的同时,有效抑制了TCP相的析出倾向。就强化元素而言,通过调控W、Mo、Re的含量,避免因难熔元素过高而导致组织失稳,通过调控Al、Ti、Nb的含量,在保证γ′相充分析出的同时,减轻成分偏析和组织不均匀性。就基体元素而言,通过调控Co、Cr的含量,在发挥固溶强化和抗腐蚀作用的同时,降低了TCP相的析出风险。
Smart Images

Figure CN122773181B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature alloy material system design and preparation technology, specifically relating to a high-purity, high-stability nickel-based single-crystal high-temperature alloy and its preparation method. Background Technology
[0002] Nickel-based single-crystal superalloys, with their excellent high-temperature creep properties, oxidation resistance, and microstructural stability, have become core materials for turbine blades and guide vanes in advanced aero-engines. In recent years, as aero-engines have continued to develop towards higher thrust-to-weight ratios and longer service life, turbine inlet temperatures have been rising, making the service environment for nickel-based single-crystal superalloys increasingly demanding.
[0003] Studies have shown that the appropriate addition of refractory elements (such as Re, Ru, W, and Mo), carbide-forming elements (such as Hf and Nb), and γ′ phase-forming elements (such as Al and Ti) can significantly improve the temperature resistance of alloys. Therefore, the content and variety of these strengthening elements in nickel-based single-crystal superalloys are increasing. However, this has also led to a series of problems: on the one hand, excessively high refractory element content can easily cause the precipitation of TCP phase in the γ matrix. The formation of TCP phase accelerates crack initiation and propagation, reduces the alloy's creep rupture performance, and shortens its creep fracture life. On the other hand, Re, Ru, and Hf are rare and precious metals, and their rapidly rising production costs severely restrict their large-scale application. Therefore, how to optimize alloy composition design to reduce dependence on rare and precious metals such as Re, Ru, and Hf while simultaneously improving the alloy's temperature resistance and microstructural stability is one of the urgent technical problems to be solved in this field.
[0004] Besides the main alloying elements, the content and form of impurity elements such as S, O, and N, as well as trace amounts of highly reactive elements such as Ce, Y, La, and Mg, also have a crucial impact on the microstructure and properties of nickel-based single-crystal superalloys. Among them, S has a very strong interfacial segregation effect. Even trace amounts of S can spontaneously accumulate in weak regions such as dendrite boundaries and subgrain boundaries, combining with Ni and Cr to form low-melting-point brittle sulfide inclusions such as Ni3S2 and CrS, significantly weakening the interfacial bonding force and thus inducing casting hot cracks and mid-temperature intergranular brittle fracture. In a gas-fired corrosive environment, S can also damage the alloy surface protection system, accelerate molten sulfate erosion, and significantly increase the crack propagation rate. Oxide (O) readily reacts with reactive elements such as Al and Hf during alloy melting and solidification, forming hard and brittle oxide inclusions such as Al2O3 and HfO2. These inclusions, remaining within the alloy, disrupt the continuity of the metal matrix, induce localized stress concentrations, and become microcrack initiation sites. They also deplete key antioxidant elements, damage the dense surface oxide film structure, exacerbate high-temperature internal oxidation, and significantly degrade the alloy's high-temperature creep strength and thermal fatigue performance. Nitrogen (N) has a strong affinity for elements such as Ti, Al, and Cr, easily precipitating high-melting-point hard nitride inclusions such as TiN and AlN. These inclusions often exist in angular shapes in dendritic boundary regions, similarly inducing stress concentrations and accelerating crack propagation.
[0005] Adding highly reactive elements such as Ce, Y, La, and Mg to nickel-based single-crystal superalloys can, on the one hand, facilitate the removal of S and O impurities from the alloy, and on the other hand, improve the alloy's high-temperature oxidation and corrosion resistance and interfacial stability. However, this is contingent on the appropriate amount and method of addition, avoiding the formation of low-melting-point harmful phases such as Ni5Ce, Ni3Y, and Ni5La, and ensuring the timely removal of deoxidation and desulfurization products; otherwise, the alloy's performance will be compromised. Therefore, how to deeply purify impurities such as S, O, and N in nickel-based single-crystal superalloys while rationally applying trace amounts of reactive elements such as Ce, Y, La, and Mg is another technical problem that urgently needs to be solved in this field.
[0006] Based on the above technical problems, there is an urgent need to develop a high-purity and high-stability nickel-based single-crystal high-temperature alloy and its preparation method. By rationally controlling the ratio of main elements, the alloy can be guaranteed to have good structural stability and high-temperature mechanical properties. By optimizing the alloy preparation process and introducing active elements such as Ce, Y, La and Mg, the deep removal of key impurity elements S, O and N can be guaranteed. Summary of the Invention
[0007] To address the problems existing in the prior art, this invention provides a high-purity, high-stability nickel-based single-crystal superalloy. The nickel-based single-crystal superalloy comprises the following chemical composition by mass percentage: C 0.12-0.18wt%, Co 8.20-10.00wt%, Cr 4.40-6.00wt%, W 11.00-12.50wt%, Mo 0.90-1.50wt%, Al 5.50-6.50wt%, Ti 0.90-1.40wt%, Nb 1.20-1.70wt%, B 0.002-0.02wt%, Hf 0.001-0.15wt%, Re 1.50-2.50wt%, with the balance being Ni and small amounts of impurity elements and highly reactive elements. Some elements must simultaneously meet the following conditions: (1) The Re content is negatively correlated with the sum of W+Mo content. Within the range of the sum of Re and W+Mo content, when the amount of Re added increases by 0.5wt%, the amount of W+Mo added decreases by 0.8-1.2wt% accordingly. (2) The C content is positively correlated with the sum of Hf+Ti+Nb content. Within the range of the sum of C content and Hf+Ti+Nb content, when the amount of C added increases by 0.03wt%, the amount of Hf+Ti+Nb added increases by 0.4-0.6wt%.
[0008] Preferably, the mass percentage of the impurity elements is controlled as follows: S ≤ 0.0002 wt%, O ≤ 0.0004 wt%, N ≤ 0.0002 wt%; the mass percentage of the highly active elements is controlled as follows: Ce ≤ 0.015 wt%, Y ≤ 0.015 wt%, La ≤ 0.02 wt%, Mg ≤ 0.005 wt%. The Mg content is positively correlated with the Hf content; within the range of Mg and Hf content, for every 0.05 wt% increase in Hf addition, the Mg addition increases by 0.001-0.0015 wt%.
[0009] This invention also provides a method for preparing a high-purity, high-stability nickel-based single-crystal superalloy, the preparation method comprising the following steps in sequence: Step 1: Place all Cr raw materials and part of Ni raw materials into an electron beam melting furnace, and melt and purify them according to the preset process parameters to obtain NiCr master alloy. Step 2: After evacuating the vacuum induction melting furnace to the preset vacuum level, add raw materials to the ceramic crucible inside the furnace in the following order: First, spread the preset proportion of C raw material evenly at the bottom of the ceramic crucible as the bottom raw material layer; then mix the remaining Ni raw material, all NiCr master alloy and all Co raw material evenly and spread them evenly on the bottom raw material layer as the middle raw material layer; finally, mix all Re raw material, all W raw material, all Mo raw material and all Nb raw material evenly and spread them evenly on the middle raw material layer as the upper raw material layer. Step 3: Heat the furnace charge according to the preset power. After the charge has completely melted and formed a molten pool, raise the temperature of the alloy melt to the refining temperature and refine it. After refining, cool the alloy melt back to the preset temperature. Step 4: Slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Ti raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt. Step 5: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Al raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float to the surface of the alloy melt. Then, immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step Six: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the preset proportion of C raw material to the alloy melt, and then add all of the Ce raw material to the alloy melt. After the feeding is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to fully float to the surface of the alloy melt. Step 7: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, then mix all the Y raw materials and all the La raw materials evenly and add them to the alloy melt; after the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 8: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The order of adding materials is as follows: first, mix all Hf raw materials and all B raw materials evenly and then add them to the alloy melt, then add all Mg raw materials to the alloy melt; after the addition is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 9: Adjust the temperature of the alloy melt to the pouring temperature and pour it. During the pouring process, multi-stage filtration is used to obtain a high-purity master alloy ingot. The master alloy ingot is remelted and directionally solidified using the spiral crystal selection method or seed crystal method to obtain a single crystal casting. The single crystal casting is subjected to solution treatment and aging treatment to finally obtain a high-purity and high-stability nickel-based single crystal high-temperature alloy casting.
[0010] Preferably, in step one, the Ni raw material added to the electron beam melting furnace accounts for 70-90 wt% of the total mass of the Ni raw material, and both the Cr and Ni raw materials are added in elemental form; the preset process parameters include: molten pool temperature 1650-1800℃, vacuum degree less than or equal to 0.1 Pa, and scanning speed 10-30 mm / min.
[0011] In any of the above schemes, it is preferred that, in step two, the vacuum degree of the vacuum induction melting furnace is less than or equal to 1 Pa; the added C raw material accounts for 30-35 wt% of the total mass of the C raw material, and the C raw material, Ni raw material, Co raw material, Re raw material, W raw material, Mo raw material and Nb raw material are all added in elemental form.
[0012] In any of the above schemes, it is preferred that in step three, the preset power is 600-800kW, the refining temperature is 1560-1600℃, the refining time is 30-90min, and after refining, the alloy melt is cooled to 1430-1470℃.
[0013] In any of the above schemes, it is preferred that in step four, the added C raw material accounts for 5-6 wt% of the total mass of C raw material, and both C raw material and Ti raw material are added in elemental form. After the feeding is completed, electromagnetic stirring is continued for 3-10 minutes.
[0014] In any of the above schemes, it is preferred that in step five, the amount of raw material C added is five times that in step four, and both raw material C and raw material Al are added in elemental form. After the feeding is completed, electromagnetic stirring is continued for 3-10 minutes.
[0015] In any of the above schemes, it is preferred that, in step six, the added C raw material accounts for 10-12 wt% of the total mass of the C raw material, the C raw material is added in elemental form, and the Ce raw material is added in the form of NiCe intermediate alloy. After the feeding is completed, electromagnetic stirring is continued for 3-10 minutes.
[0016] In any of the above schemes, it is preferred that in step seven, the amount of C material added is twice that added in step six, the C material is added in elemental form, and the Y material and La material are added in the form of NiY master alloy and NiLa master alloy, respectively. After the feeding is completed, electromagnetic stirring is continued for 3-10 minutes.
[0017] In any of the above schemes, it is preferred that in step eight, both Hf raw material and B raw material are added in elemental form, and Mg raw material is added in NiMg intermediate alloy form. After the feeding is completed, electromagnetic stirring is continued for 3-10 minutes.
[0018] In any of the above embodiments, preferably, in steps five, seven, and eight, the thickness of the porous ceramic plate is 20-30 mm, and its diameter is 0.7-0.9 times the inner diameter of the ceramic crucible; the porous ceramic plate has a multi-layer irregular pore structure with a pore density of not less than 10 PPI; the material of the porous ceramic plate is any one of zirconium oxide, alumina, or yttrium oxide.
[0019] The porous ceramic plate needs to be baked before use. The baking temperature is 1000-1100℃ and the baking time is 4-8 hours. The porous ceramic plate is immersed in the surface of the alloy melt to adsorb inclusions for 3-5 seconds, and then the porous ceramic plate is slowly removed.
[0020] In any of the above schemes, it is preferred that, in step nine, at least three levels of filter screens are sequentially and spaced apart inside the trough-shaped gating channel along the flow direction of the alloy liquid, namely, the first level filter screen, the second level filter screen, ..., the (N-1)th level filter screen and the Nth level filter screen. Each level of filter screen has a multi-layer irregular pore structure and is made of ceramic-based material.
[0021] The pore density of each filter screen must meet the following conditions: the pore density of the first-stage filter screen is the lowest, not less than 10 PPI; the pore density of the (N-1)th-stage filter screen is the highest, not less than 30 PPI; except for the first-stage filter screen and the (N-1)th-stage filter screen, the pore density of the remaining filter screens increases sequentially along the flow direction of the alloy liquid.
[0022] In any of the above schemes, it is preferred that, in step nine, during the preparation stage of the master alloy ingot, the casting temperature is 1480-1540℃; during the directional solidification stage, the refining temperature is 1600-1640℃, the upper heater temperature is 1500-1540℃, the lower heater temperature is 1520-1560℃, the casting temperature is 1520-1560℃, and the pulling rate after casting is 2-5mm / min.
[0023] Solution treatment regime: First, perform solution treatment at 1180-1200℃ for 1-3 hours, then increase the temperature to 1250-1270℃ at a rate not exceeding 5℃ / min for 2-6 hours of solution treatment, followed by air cooling to room temperature. Aging treatment regime: First, perform high-temperature aging treatment at 1070-1100℃ for 1-3 hours, followed by air cooling to room temperature; then, perform low-temperature aging treatment at 850-880℃ for 18-32 hours, followed by air cooling to room temperature.
[0024] The alloy composition of this invention is designed synergistically around three aspects: alloy cleanliness, microstructure stability, and service performance. The specific principle is as follows: Sulfur (S) is a high-risk impurity element in nickel-based single-crystal superalloys, exhibiting strong interfacial segregation characteristics. It readily accumulates at dendrite and subgrain boundaries, forming low-melting-point sulfides and complex inclusions with elements such as Ni and Cr. This severely weakens interfacial bonding strength, inducing thermal cracking and intergranular brittle fracture, while accelerating molten salt corrosion and significantly reducing the alloy's mid-temperature toughness, thermal fatigue, and long-term service stability. Oxygen (O) is also a typical harmful element. During melting and solidification, it readily reacts with reactive elements such as Al and Hf to form oxide inclusions, disrupting the matrix structure and causing localized stress concentration. This not only degrades the alloy's high-temperature durability and thermal fatigue resistance but also damages the dense oxide film structure, weakening its oxidation protection capabilities. Nitrogen (N) is also a harmful impurity that requires strict control. It readily combines with Ti, Al, and Cr to form high-melting-point hard nitride inclusions, impairing the alloy's high-temperature service performance. Therefore, this invention strictly limits the content of S, O, and N impurities in the alloy to S ≤ 0.0002%, O ≤ 0.0004%, and N ≤ 0.0002%.
[0025] The roles of carbon (C) and boron (B) in nickel-based single-crystal superalloys are complex. First-generation single-crystal superalloys completely remove C and B, while second-generation and later single-crystal superalloys incorporate small amounts of C and B to strengthen small-angle grain boundaries. This invention, after considering multiple factors, determines to incorporate a relatively high content of C (0.12-0.18%): First, C is the purest deoxidizer during vacuum induction melting, with the deoxidation product CO escaping in gaseous form, which facilitates the synergistic removal of other impurities such as sulfur (S) and nitrogen (N). Second, the carbides formed by C with elements such as hydrogen peroxide (Hf), nitrogen (Nb), and titanium (Ti) can exert a high-temperature strengthening effect. Furthermore, the addition of C helps reduce the number of electron vacancies in the alloy, thereby improving the alloy's structural stability. Regarding boron, trace amounts improve the high-temperature service performance and structural stability of nickel-based single-crystal superalloys, but studies have shown that when the content exceeds 0.02%, large-size and low-melting-point borides are easily formed. Therefore, this invention controls the B content within the range of 0.002-0.02%.
[0026] Co and Cr have atomic radii close to Ni, allowing them to dissolve extensively in the γ-matrix and induce moderate lattice distortion, which is beneficial for improving the high-temperature performance of nickel-based single-crystal superalloys. Cr is crucial for the oxidation and corrosion resistance of nickel-based single-crystal superalloys; however, Cr is also a typical TCP phase promoter, and excessive addition can easily damage the microstructure stability. While Co can effectively exert solid solution strengthening, its economic cost is higher than that of Ni. Considering both performance requirements and cost factors, this invention controls the Co content within the range of 8.20-10.00% and the Cr content within the range of 4.40-6.00%.
[0027] W and Mo are key solid solution strengthening elements in nickel-based single-crystal superalloys, but both increase the risk of TCP phase precipitation. Therefore, this invention appropriately reduced the content of W and Mo elements while ensuring high-temperature strength. After comprehensive evaluation, the W content was finally determined to be 11.00-12.50% and the Mo content to be 0.90-1.50%.
[0028] Resin (Re) is crucial for the high-temperature service performance of nickel-based single-crystal superalloys. Typically, first-generation single-crystal alloys contain no Re, second-generation alloys contain 1.50-3.00% Re, and third-generation alloys contain 4.00-6.00% Re. However, as the Re content increases, the precipitation of the TCP phase in the alloy becomes increasingly severe. Based on previous theoretical and experimental results, this invention comprehensively evaluates the impact of Re content on the high-temperature service performance and microstructural stability of the alloy under the proposed composition system, ultimately controlling the Re content to be between 1.50-2.50%.
[0029] In nickel-based single-crystal superalloys, hydrogen sulfide (Hf) can form stable MC carbides and accumulate at small-angle grain boundaries and the γ′ phase, which is beneficial for improving the high-temperature service performance of the alloy. However, Hf is a strongly positive segregating element; high content can lead to an expansion of the solid-liquid two-phase region, a significant increase in the (γ+γ′) eutectic phase content, and an intensified tendency for TCP phase precipitation. Therefore, the Hf content must be strictly limited. Based on theoretical calculations and experimental results, this invention controls the Hf content to 0.001-0.15%.
[0030] Al, Ti, and Nb are key elements forming the γ′ strengthening phase in nickel-based single-crystal superalloys. Ti and Nb are also key carbide-forming elements, and all three are crucial to the high-temperature performance of the alloy. However, higher Al content tends to exacerbate TCP phase precipitation, while excessively high Ti and Nb content can worsen compositional segregation and microstructure inhomogeneity. Considering both strengthening effect and microstructure stability, this invention determines the Al content to be 5.50-6.50%, the Ti content to be 0.90-1.40%, and the Nb content to be 1.20-1.70%.
[0031] The addition of trace amounts of highly reactive elements Ce, Y, La, and Mg can effectively bind O and S elements in nickel-based single-crystal superalloys and also improve the alloy's oxidation resistance and corrosion resistance. However, the oxides and sulfides of Ce, Y, and La are prone to polymerization and growth, and Mg oxide has high hardness; if they remain in the alloy, they may cause serious damage. In addition, excessive Ce, Y, and La content can easily form low-melting-point, easily oxidized and corroded rare-earth-rich phases in the alloy. Therefore, while utilizing their deep purification effect, this invention controls the retention amounts of Ce, Y, La, and Mg in the alloy to no more than 0.015%, 0.015%, 0.02%, and 0.005%, respectively, to avoid the formation of harmful phases.
[0032] In the preparation process of nickel-based single-crystal superalloys: for Cr raw materials, which easily introduce nitrogen (N) and Ni raw materials, which are used in the largest quantity, vacuum electron beam melting is used to purify and prepare NiCr master alloys. This is because during vacuum induction melting, N is mainly removed in the form of gaseous overflow. Currently, the vacuum level of vacuum induction equipment cannot guarantee the depth of removal. Further increasing the vacuum level will not only increase production costs but also exacerbate the decomposition of crucible refractory materials. In contrast, vacuum electron beam melting has a good removal effect on N, but this equipment is not conducive to precise control of the composition ratio of the master alloy. Therefore, this invention uses vacuum electron beam melting to pre-purify Cr and Ni, reducing the introduction of N from the source, and then uses vacuum induction melting to prepare the master alloy.
[0033] The raw materials for Ce, Y, La, and Mg are NiCe, NiLa, NiY, and NiMg master alloys. This is because Ce, Y, La, and Mg have high chemical reactivity, high saturated vapor pressure, and are significantly lighter than the alloy liquid. Adding them directly in elemental form would result in severe burn-off and make it difficult for them to penetrate the alloy liquid.
[0034] The C element content is high and added in stages according to a specific ratio, especially when it is added together with active elements such as Ti, Al, Ce, Y, and La. This is to reduce the unnecessary oxidation of active elements such as Ti, Al, Ce, Y, and La, and at the same time, the removal of endogenous oxides and sulfide inclusions of Al, Ti, Ce, Y, and La is accelerated by the floating process of CO bubbles, which are the products of vacuum carbon deoxidation.
[0035] During the addition of Hf raw materials, C raw materials are not used in combination with Mg raw materials. This is because C and Hf elements readily react to form high-melting-point, high-density HfC residues in the alloy liquid. During the solidification process of the alloy, these residues preferentially grow, thereby deteriorating the uniformity of the microstructure. Meanwhile, the strong reducing properties and high saturated vapor pressure of Mg can effectively prevent the oxidation of Hf and promote the floating of inclusions.
[0036] The alloying process follows the order of Ti, Al, Ce, Y / La, and Hf / B / Mg. This is mainly because Al content is high, and adding Al first would cause a severe aluminothermic reaction, leading to a significant increase in the alloy melt temperature and severe splashing during Ti addition. Furthermore, the deoxidizing ability is Y > Ce ≥ La, and the desulfurizing ability is La > Ce > Y. Adding Ce first helps to reduce O and S impurities in the alloy melt to a lower level, while adding Y and La later allows them to exert their respective deep deoxidation and desulfurization capabilities. The density of Ce is 6.77 g / cm³. 3 >La (6.15g / cm) 3 ) > Y (4.47 g / cm 3 Adding Ce first, followed by Y and La, helps high-density Ce-containing inclusions float to the surface. Furthermore, Hf-containing inclusions have a much higher density than the molten alloy; once formed, they cannot float independently. Adding Hf last minimizes their formation as inclusions. Additionally, Mg has stronger reducing properties than Hf, and the large number of bubbles generated during vaporization helps Hf-containing inclusions float and dissipate, providing effective protection.
[0037] After adding Al / Ti, Ce / Y / La, and Hf / Mg / B, porous ceramic plates are periodically immersed in the alloy melt to adsorb inclusions that float to the surface. This is because Ce, Y, and La have stronger reducing properties than Al and Ti. Although Hf has weaker reducing properties than Ce, Y, and La, Hf-containing inclusions have a higher density than the alloy melt, making them prone to remaining inside the melt once formed. Periodically removing surface inclusions can suppress the formation of complex rare-earth-containing inclusions and high-density Hf-containing inclusions. Furthermore, the porous ceramic plates are preferably made of zirconium oxide and require baking before use to prevent reaction with the alloy melt. The design of the ceramic plate's pore density and size ensures effective impurity removal while mitigating the risk of breakage. The porous ceramic adsorption plates are installed inside the vacuum induction melting furnace and can be moved vertically.
[0038] During the casting stage of the master alloy, ceramic-based filters with a filtration level of no less than three and a minimum pore density of no less than 10 PPI are used. The filters are arranged from low to high pore density to further filter out inclusions that fall off the crucible wall and high-density inclusions such as hafnium oxide inclusions that cannot float sufficiently. Among them, the N-1 level filter has the highest pore density, no less than 30 PPI, to ensure the filtration of inclusions while preventing the filter from breaking.
[0039] The nickel-based single-crystal superalloy of this invention is independently designed based on the first and second generation alloys. It does not belong to the existing grade category, but is an independent non-standard alloy.
[0040] In this invention, raw material C is added gradually in batches. Step two: Raw material C is added together with raw materials Ni, Co, Re, W, Mo, and Nb, accounting for 30-35 wt% of the total mass of raw material C. Step four: Raw material C is added together with raw material Ti, accounting for 5-6 wt% of the total mass of raw material C. Step five: Raw material C is added together with raw material Al, at a rate five times that of raw material C added in step four. Step six: Raw material C is added together with raw material Ce, accounting for 10-12 wt% of the total mass of raw material C. Step seven: Raw material C is added together with raw materials Y and La, at a rate twice that of raw material C added in step six.
[0041] In the above-described addition scheme, the amount of C raw material added in steps two and four, and steps five and six and steps seven is roughly equal, each accounting for about one-third of the total mass of C raw material. Specifically, the amount of C raw material added in steps four and five is allocated based on the Ti and Al content, while the amount added in steps six and seven is allocated based on the activity and content of Ce, Y, and La. In all the above steps, the order of adding C raw material first, followed by the other raw materials, is adopted to utilize the deoxidizing effect of C to protect the other raw materials from oxidation.
[0042] The present invention relates to a high-purity, high-stability nickel-based single-crystal superalloy and its preparation method, which has the following beneficial effects: (1) This invention effectively suppresses the precipitation tendency of the TCP phase while ensuring solid solution strengthening and γ′ phase precipitation strengthening by reasonably controlling the content range of strengthening elements and matrix elements. Regarding strengthening elements, by controlling the content of W, Mo, and Re, the microstructure instability caused by excessive refractory elements is avoided. By controlling the content of Al, Ti, and Nb, the compositional segregation and microstructure inhomogeneity are reduced while ensuring sufficient precipitation of the γ′ phase. Regarding matrix elements, by controlling the content of Co and Cr, the risk of TCP phase precipitation is reduced while exerting solid solution strengthening and corrosion resistance.
[0043] (2) The present invention strictly limits the content of three harmful impurity elements, S, O and N. By deeply removing the impurity elements, the formation of low melting point sulfides, hard and brittle oxides and angular nitride inclusions is effectively avoided, the hidden dangers of interface weakening and stress concentration are eliminated, and the interface bonding strength, medium temperature toughness, thermal fatigue performance and long-term service stability of the alloy are significantly improved.
[0044] (3) By adding highly active trace elements such as Ce, Y, La, and Mg, and strictly controlling their retention in the alloy (Ce≤0.015%, Y≤0.015%, La≤0.02%, Mg≤0.005%), this invention fully utilizes their deep deoxidation and desulfurization and improves their antioxidant and corrosion resistance properties, while effectively avoiding the formation of harmful phases such as low-melting-point rare earth-rich phases, large-size oxide / sulfide polymers, and high-hardness MgO residues due to excessive content, thus achieving synergistic optimization of deep purification and structural stability.
[0045] (4) This invention designs an alloying sequence of Ti→Al→Ce→Y / La→Hf / B / Mg, fully considering multiple factors such as aluminothermic reaction control, deoxidation and desulfurization capacity gradient, inclusion density difference, and flotation removal efficiency. Ce is added first to reduce O and S to a lower level, followed by Y and La to exert a deep deoxidation and desulfurization effect; the density difference is used to promote the full flotation of high-density Ce-containing inclusions; Hf is added last, and the gasification of Mg generates bubbles to assist the removal of Hf-containing inclusions, minimizing inclusion residue. At the same time, C raw materials are added in batches, with C raw materials added first in each step, using the deoxidation effect of C to protect other alloying elements from oxidation.
[0046] (5) Through the synergistic optimization of composition design and preparation process, this invention achieves a balance of high cleanliness, good structural stability and excellent high temperature mechanical properties of nickel-based single crystal high temperature alloys, which are particularly suitable for the manufacture of advanced aero-engine working blades or guide blades. Attached Figure Description
[0047] Figure 1 This is a schematic diagram of the process of a porous ceramic plate adsorbing inclusions in a preferred embodiment of the high-purity and high-stability nickel-based single-crystal superalloy and its preparation method according to the present invention; Figure 2 for Figure 1 The diagram shows a multi-stage filtration process during the alloy liquid casting process in the embodiment shown. Figure 3 for Figure 1 Morphology of inclusions adsorbed on porous ceramic plates after the addition of Ti and Al in the illustrated embodiment; Figure 4 for Figure 1 The morphology of inclusions on the surface of the alloy liquid before multi-stage filtration in the embodiment shown; Figure 5 for Figure 1 The morphology of inclusions on the surface of the alloy liquid after primary filtration in the illustrated embodiment is shown. Figure 6 for Figure 1 The morphology of inclusions on the surface of the alloy liquid after secondary filtration in the illustrated embodiment is shown. Figure 7for Figure 1 The morphology of inclusions on the surface of the alloy liquid after three-stage filtration in the embodiment shown; Figure 8 Comparative diagrams show the as-cast microstructures of single-crystal test rods prepared in Examples 1, 2, and 2. Figure 9 Comparative diagrams show the microstructure of single crystal specimens prepared in the heat-treated state according to Examples 1, 2, and 2. Detailed Implementation
[0048] To further understand the invention, the following detailed description of the invention will be provided in conjunction with specific embodiments.
[0049] Example 1: According to a preferred embodiment of the high-purity, high-stability nickel-based single-crystal superalloy of the present invention, the nickel-based single-crystal superalloy comprises the following chemical composition by mass percentage: C 0.12wt%, Co 8.20wt%, Cr 4.40wt%, W 12.50wt%, Mo 1.50wt%, Al 5.50wt%, Ti 0.90wt%, Nb 1.20wt%, B 0.002wt%, Hf 0.001wt%, Re 1.50wt%, with the balance being Ni and trace amounts of impurity elements and highly reactive elements; the mass percentage of the impurity elements is controlled as follows: S≤0.0002wt%, O≤0.0004wt%, N≤0.0002wt%; the mass percentage of the highly reactive elements is controlled as follows: Ce≤0.015wt%, Y≤0.015wt%, La≤0.02wt%, Mg≤0.005wt%. Some elements must simultaneously meet the following conditions: (1) The Re content is negatively correlated with the sum of W+Mo content. Within the range of the sum of Re and W+Mo content, when the amount of Re added increases by 0.5wt%, the amount of W+Mo added decreases by 0.8-1.2wt% accordingly. (2) The C content is positively correlated with the sum of Hf+Ti+Nb content. Within the range of the sum of C content and Hf+Ti+Nb content, for every 0.03wt% increase in the amount of C added, the amount of Hf+Ti+Nb added increases by 0.4-0.6wt% accordingly. (3) The Mg content is positively correlated with the Hf content. Within the range of Mg and Hf content, when the amount of Hf added increases by 0.05wt%, the amount of Mg added increases by 0.001-0.0015wt%.
[0050] In this embodiment, the minimum addition amount of Re is 1.5 wt%, the maximum addition amount of W+Mo is 14 wt%, the minimum addition amount of C is 0.12 wt%, the minimum addition amount of Hf+Ti+Nb is 2.101 wt%, the minimum addition amount of Hf is 0.001 wt%, and the addition amount of Mg is 0.0025 wt%.
[0051] This embodiment also provides a method for preparing a high-purity, high-stability nickel-based single-crystal superalloy, the preparation method comprising the following steps in sequence: Step 1: Place all Cr raw materials and part of Ni raw materials into an electron beam melting furnace, and melt and purify them according to the preset process parameters to obtain NiCr master alloy. Step 2: After evacuating the vacuum induction melting furnace to the preset vacuum level, add raw materials to the ceramic crucible inside the furnace in the following order: First, spread the preset proportion of C raw material evenly at the bottom of the ceramic crucible as the bottom raw material layer; then mix the remaining Ni raw material, all NiCr master alloy and all Co raw material evenly and spread them evenly on the bottom raw material layer as the middle raw material layer; finally, mix all Re raw material, all W raw material, all Mo raw material and all Nb raw material evenly and spread them evenly on the middle raw material layer as the upper raw material layer. Step 3: Heat the furnace charge according to the preset power. After the charge has completely melted and formed a molten pool, raise the temperature of the alloy melt to the refining temperature and refine it. After refining, cool the alloy melt back to the preset temperature. Step 4: Slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Ti raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to fully float to the surface of the alloy melt. Step 5: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Al raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float to the surface of the alloy melt. Then, immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step Six: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the preset proportion of C raw material to the alloy melt, and then add all of the Ce raw material to the alloy melt. After the feeding is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to fully float to the surface of the alloy melt. Step 7: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, then mix all the Y raw materials and all the La raw materials evenly and add them to the alloy melt; after the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 8: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The order of adding materials is as follows: first, mix all Hf raw materials and all B raw materials evenly and then add them to the alloy melt, then add all Mg raw materials to the alloy melt; after the addition is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 9: Adjust the temperature of the alloy melt to the pouring temperature and pour it. During the pouring process, multi-stage filtration is used to obtain a high-purity master alloy ingot. The master alloy ingot is remelted and directionally solidified using the spiral crystal selection method or seed crystal method to obtain a single crystal casting. The single crystal casting is subjected to solution treatment and aging treatment to finally obtain a high-purity and high-stability nickel-based single crystal high-temperature alloy casting.
[0052] In step one, the Ni raw material added to the electron beam melting furnace accounts for 80 wt% of the total mass of Ni raw material, and both Cr and Ni raw materials are added in elemental form; the preset process parameters include: molten pool temperature 1725℃, vacuum degree less than or equal to 0.1 Pa, and scanning speed 20 mm / min.
[0053] In step two, the vacuum degree of the vacuum induction melting furnace is less than or equal to 1 Pa; the added C raw material accounts for 34 wt% of the total mass of C raw material, and C raw material, Ni raw material, Co raw material, Re raw material, W raw material, Mo raw material and Nb raw material are all added in elemental form.
[0054] In step three, the preset power is 700kW, the refining temperature is 1580℃, the refining time is 60min, and after refining, the alloy melt is cooled to 1450℃.
[0055] In step four, the added C raw material accounts for 5.5 wt% of the total mass of C raw material. Both C and Ti raw materials are added in elemental form. After the feeding is completed, electromagnetic stirring continues for 6.5 min.
[0056] In step five, the amount of raw material C added is five times that added in step four (27.5 wt%). Both raw material C and raw material Al are added in elemental form. After the feeding is completed, electromagnetic stirring continues for 6.5 min.
[0057] In step six, the added C raw material accounts for 11 wt% of the total mass of C raw material. The C raw material is added in elemental form, and the Ce raw material is added in the form of NiCe master alloy. After the feeding is completed, electromagnetic stirring continues for 6.5 min.
[0058] In step seven, the amount of C material added is twice that added in step six (22wt%). The C material is added in elemental form, while the Y material and La material are added in the form of NiY master alloy and NiLa master alloy, respectively. After the feeding is completed, electromagnetic stirring continues for 6.5 minutes.
[0059] In step eight, Hf and B raw materials are added in elemental form, and Mg raw material is added in NiMg master alloy form. After the feeding is completed, electromagnetic stirring continues for 6.5 minutes.
[0060] In steps five, seven, and eight, the porous ceramic plate has a thickness of 25 mm and a diameter 0.8 times the inner diameter of the ceramic crucible. The porous ceramic plate has a multi-layered irregular pore structure with a pore density of not less than 10 PPI, and its material is preferably zirconium oxide. Before use, the porous ceramic plate needs to be baked at 1050℃ for 6 hours. The porous ceramic plate is then immersed in the surface of the alloy melt to adsorb inclusions for 4 seconds, after which it is slowly removed.
[0061] In step nine, three levels of filters are sequentially and spaced apart inside the trough-shaped gating system along the flow direction of the molten alloy: a first-level filter, a second-level filter, and a third-level filter. Each level of filter has a multi-layered irregular pore structure and is made of ceramic-based material. The first-level filter has a minimum pore density of 10 PPI, the second-level filter has a maximum pore density of 30 PPI, and the third-level filter has a pore density of 20 PPI.
[0062] During the preparation stage of the master alloy ingot, the casting temperature was 1510℃; during the directional solidification stage, the refining temperature was 1620℃, the upper heater temperature was 1520℃, the lower heater temperature was 1540℃, the casting temperature was 1540℃, and the pulling rate after casting was 3.5mm / min.
[0063] Solution treatment regime: First, perform solution treatment at 1190℃ for 2 hours, then increase the temperature to 1260℃ at a rate not exceeding 5℃ / min for 4 hours of solution treatment, followed by air cooling to room temperature. Aging treatment regime: First, perform high-temperature aging treatment at 1085℃ for 2 hours, followed by air cooling to room temperature; then perform low-temperature aging treatment at 865℃ for 25 hours, followed by air cooling to room temperature.
[0064] In this embodiment, the process of the porous ceramic plate adsorbing inclusions is illustrated as follows: Figure 1 As shown, the multi-stage filtration process during alloy molten metal pouring is illustrated in the diagram. Figure 2 As shown, the morphology of the inclusions adsorbed on the porous ceramic plate after the addition of Ti and Al is as follows. Figure 3 As shown, the morphology of inclusions on the surface of the alloy liquid before and after multi-stage filtration is as follows: Figures 4-7 As shown. From Figure 3 It can be seen that a large number of inclusions are adsorbed on the surface of the porous ceramic plate. From Figures 4-7 It can be seen that before filtration, there are many agglomerated oxide inclusions of elements such as Al, Mg, and Hf on the alloy surface, as well as some large sub-millimeter-sized magnesium oxide particles, which may be caused by crucible sand shedding. After primary filtration, the agglomerated inclusions are greatly reduced, and the large sub-millimeter-sized inclusions disappear. With the increase of filtration stages, the cleanliness of the alloy surface continues to improve.
[0065] This embodiment achieves a balance of high purity, good structural stability, and excellent high-temperature mechanical properties in nickel-based single-crystal superalloys through synergistic optimization of composition design and preparation process, making it particularly suitable for the manufacture of advanced aero-engine working blades or guide vanes.
[0066] Example 2: According to another preferred embodiment of the high-purity, high-stability nickel-based single-crystal superalloy and its preparation method of the present invention, its material system, preparation method, technical principle, and beneficial effects are basically the same as those of Embodiment 1, except that: The nickel-based single-crystal superalloy comprises the following chemical composition by mass percentage: C 0.15wt%, Co 9.10wt%, Cr 5.20wt%, W 11.70wt%, Mo 1.10wt%, Al 6.00wt%, Ti 1.15wt%, Nb 1.40wt%, B 0.011wt%, Hf 0.051wt%, Re 2.00wt%, with the balance being Ni and trace amounts of impurity elements and highly reactive elements. The mass percentage of the impurity elements is controlled as follows: S≤0.0002wt%, O≤0.0004wt%, N≤0.0002wt%. The mass percentage of the highly reactive elements is controlled as follows: Ce≤0.015wt%, Y≤0.015wt%, La≤0.02wt%, Mg≤0.005wt%. Some elements must simultaneously meet the following conditions: (1) The Re content is negatively correlated with the sum of W+Mo content. Within the range of the sum of Re content and W+Mo content, when the amount of Re added increases by 0.5wt%, the amount of W+Mo added decreases by 1.2wt% accordingly, ensuring that it is within the range of 0.8-1.2wt%. (2) The C content is positively correlated with the sum of Hf+Ti+Nb content. Within the range of the sum of C content and Hf+Ti+Nb content, when the amount of C added increases by 0.03wt%, the amount of Hf+Ti+Nb added increases by 0.5wt% accordingly, ensuring that it is within the range of 0.4-0.6wt%. (3) The Mg content is positively correlated with the Hf content. Within the range of Mg and Hf content, when the amount of Hf added increases by 0.05wt%, the amount of Mg added increases by 0.0012wt% accordingly, ensuring that it is within the range of 0.001-0.0015wt%. In this embodiment, the amount of Mg added is 0.0037wt%.
[0067] In step one, the Ni raw material added to the electron beam melting furnace accounts for 70 wt% of the total mass of the Ni raw material, the molten pool temperature is 1650℃, and the scanning speed is 10 mm / min.
[0068] In step two, the added C raw material accounts for 34 wt% of the total mass of C raw material.
[0069] In step three, the preset power is 600kW, the refining temperature is 1560℃, the refining time is 90min, and after refining, the alloy melt is cooled to 1430℃.
[0070] In step four, the added raw material C accounts for 5 wt% of the total mass of raw material C, and electromagnetic stirring continues for 3 minutes after the feeding is completed.
[0071] In step five, the amount of raw material C added is five times (25wt%) that of raw material C added in step four. After the feeding is completed, continue electromagnetic stirring for 3 minutes.
[0072] In step six, the added raw material C accounts for 12 wt% of the total mass of raw material C. After the feeding is completed, continue electromagnetic stirring for 3 minutes.
[0073] In step seven, the amount of raw material C added is twice that added in step six (24wt%), and electromagnetic stirring continues for 3 minutes after the feeding is completed.
[0074] In step eight, after adding Hf raw materials, B raw materials and Mg raw materials, continue electromagnetic stirring for 3 minutes.
[0075] In steps five, seven, and eight, the porous ceramic plate has a thickness of 20 mm and a diameter that is 0.7 times the inner diameter of the ceramic crucible; the baking temperature is 1000℃, the baking time is 8 h, and the inclusion adsorption time is 3 s.
[0076] In step nine, during the preparation of the master alloy ingot, the casting temperature is 1480℃; during the directional solidification stage, the refining temperature is 1600℃, the upper heater temperature is 1500℃, the lower heater temperature is 1520℃, the casting temperature is 1520℃, and the post-casting pulling rate is 2mm / min. Solution treatment regime: First, solution treatment is performed at 1180℃ for 3 hours, then the temperature is increased to 1250℃ at a rate not exceeding 5℃ / min for 6 hours of solution treatment, followed by air cooling to room temperature. Aging treatment regime: First, high-temperature aging treatment is performed at 1070℃ for 3 hours, followed by air cooling to room temperature; then, low-temperature aging treatment is performed at 850℃ for 32 hours, followed by air cooling to room temperature.
[0077] Example 3: According to another preferred embodiment of the high-purity, high-stability nickel-based single-crystal superalloy and its preparation method of the present invention, its material system, preparation method, technical principle, and beneficial effects are basically the same as those of Embodiment 1, except that: The nickel-based single-crystal superalloy comprises the following chemical composition by mass percentage: C 0.18wt%, Co 10.00wt%, Cr 6.00wt%, W 11.00wt%, Mo 0.90wt%, Al 6.50wt%, Ti 1.40wt%, Nb 1.70wt%, B 0.02wt%, Hf 0.101wt%, Re 2.50wt%, with the balance being Ni and trace amounts of impurity elements and highly reactive elements. The mass percentage of the impurity elements is controlled as follows: S≤0.0002wt%, O≤0.0004wt%, N≤0.0002wt%. The mass percentage of the highly reactive elements is controlled as follows: Ce≤0.015wt%, Y≤0.015wt%, La≤0.02wt%, Mg≤0.005wt%. Some elements must simultaneously meet the following conditions: (1) The Re content is negatively correlated with the sum of W+Mo content. Within the range of the sum of Re content and W+Mo content, when the amount of Re added increases by 0.5wt%, the amount of W+Mo added decreases by 0.9wt% accordingly, ensuring that it is within the range of 0.8-1.2wt%. (2) The C content is positively correlated with the sum of Hf+Ti+Nb content. Within the range of the sum of C content and Hf+Ti+Nb content, when the amount of C added increases by 0.03wt%, the amount of Hf+Ti+Nb added increases by 0.6wt% accordingly, ensuring that it is within the range of 0.4-0.6wt%. (3) The Mg content is positively correlated with the Hf content. Within the range of Mg and Hf content, when the amount of Hf added increases by 0.05wt%, the amount of Mg added increases by 0.0013wt% accordingly, ensuring that it is within the range of 0.001-0.0015wt%. In this embodiment, the amount of Mg added is 0.005wt%.
[0078] In step one, the Ni raw material added to the electron beam melting furnace accounts for 90 wt% of the total mass of Ni raw material, the molten pool temperature is 1800℃, and the scanning speed is 30 mm / min.
[0079] In step two, the added C raw material accounts for 31 wt% of the total mass of C raw material.
[0080] In step three, the preset power is 800kW, the refining temperature is 1600℃, the refining time is 30min, and after refining, the alloy melt is cooled to 1470℃.
[0081] In step four, the added raw material C accounts for 6 wt% of the total mass of raw material C, and electromagnetic stirring continues for 10 minutes after the feeding is completed.
[0082] In step five, the amount of raw material C added is five times (30wt%) that of raw material C added in step four. After the feeding is completed, continue electromagnetic stirring for 10 minutes.
[0083] In step six, the added raw material C accounts for 11 wt% of the total mass of raw material C. After the feeding is completed, continue electromagnetic stirring for 10 minutes.
[0084] In step seven, the amount of raw material C added is twice that added in step six (22wt%). After the feeding is completed, continue electromagnetic stirring for 10 minutes.
[0085] In step eight, after adding Hf raw materials, B raw materials and Mg raw materials, continue electromagnetic stirring for 10 minutes.
[0086] In steps five, seven, and eight, the porous ceramic plate has a thickness of 30 mm and a diameter that is 0.9 times the inner diameter of the ceramic crucible; the baking temperature is 1100℃, the baking time is 4 h, and the inclusion adsorption time is 5 s.
[0087] In step nine, during the preparation of the master alloy ingot, the casting temperature is 1540℃; during the directional solidification stage, the refining temperature is 1640℃, the upper heater temperature is 1540℃, the lower heater temperature is 1560℃, the casting temperature is 1560℃, and the post-casting pulling rate is 5mm / min. Solution treatment regime: First, solution treatment is performed at 1200℃ for 1 hour, then the temperature is increased to 1270℃ at a rate not exceeding 5℃ / min for 2 hours of solution treatment, followed by air cooling to room temperature. Aging treatment regime: First, high-temperature aging treatment is performed at 1100℃ for 1 hour, followed by air cooling to room temperature; then, low-temperature aging treatment is performed at 880℃ for 18 hours, followed by air cooling to room temperature.
[0088] Comparative Example 1: Compared with the examples, the material system of Comparative Example 1 does not contain Ce, Y, La, or Mg elements, does not have the smelting and purification process of Cr and Ni, adds all C raw materials at once in the initial stage of vacuum induction melting, does not use porous ceramic plates to adsorb inclusions during the addition of raw materials, does not have a multi-stage filtration process during casting, and other processes and parameters are basically the same as those of Example 1.
[0089] Comparative Example 2: Compared with the examples, the material system of Comparative Example 2 does not contain Re and Hf elements, while the other elements and their contents, preparation process and parameters are basically the same as those of Example 1.
[0090] The above embodiments and comparative examples were tested and analyzed, and the test results are as follows: Figure 8 , Figure 9 Tables 1 and 2 show the microstructures of the single-crystal test rods prepared in Example 1, Example 2, and Comparative Example 2 in their as-cast and heat-treated states, respectively. Figure 8 and Figure 9 As shown. First, it can be observed that both the examples and the comparative examples contain a large amount of (γ+γ′) eutectic phase in the as-cast state, and the eutectic phase is effectively dissolved after heat treatment. Second, it can be observed that neither the examples nor the comparative examples contain TCP phase in the as-cast state, but a small amount of TCP phase precipitates after heat treatment. In addition, it can be observed that the γ′ strengthening phase of the examples is significantly smaller and more cubic than that of the comparative examples.
[0091] The comparison results of the S, O, and N impurity element contents in the alloys of the examples and comparative examples are shown in Table 1, and the comparison results of the mechanical properties of the single crystal castings of the examples and comparative examples are shown in Table 2.
[0092]
[0093]
[0094] As can be seen from Tables 1 and 2, the content of S, O, and N impurity elements in the alloys of the examples is significantly lower than that of Comparative Example 1. At the same time, the mechanical properties of the single crystal castings (whether as-cast or heat-treated) in the examples are significantly higher than those in the comparative example.
[0095] Special Note: The technical solution of this invention involves numerous parameters, and the synergistic effects between these parameters must be comprehensively considered to achieve the beneficial effects and significant progress of this invention. Furthermore, the value ranges of each parameter in the technical solution were obtained through extensive experimentation. For each parameter and the combinations thereof, the inventors have recorded a large amount of experimental data; however, due to space limitations, the specific experimental data is not disclosed here.
[0096] It will be readily understood by those skilled in the art that this invention includes any combination of the inventive description and specific embodiments outlined in the foregoing specification, as well as the various parts shown in the accompanying drawings. Due to space limitations and for the sake of brevity, not all of these combinations have been described in detail. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A high-purity, high-stability nickel-based single-crystal superalloy, characterized in that, The nickel-based single-crystal superalloy comprises the following chemical composition by mass percentage: C 0.12-0.18wt%, Co 8.20-10.00wt%, Cr 4.40-6.00wt%, W 11.00-12.50wt%, Mo 0.90-1.50wt%, Al 5.50-6.50wt%, Ti 0.90-1.40wt%, Nb 1.20-1.70wt%, B 0.002-0.02wt%, Hf 0.001-0.15wt%, Re 1.50-2.50wt%, with the balance being Ni and trace amounts of impurity elements and highly reactive elements; the highly reactive elements are Ce, Y, La, and Mg, with their mass percentages controlled as follows: Ce ≤ 0.015wt%, Y ≤ 0.015wt%, La ≤ 0.02wt%, Mg ≤ 0.005wt%; some elements must simultaneously meet the following conditions: (1) The Re content is negatively correlated with the sum of W+Mo content. Within the range of the sum of Re and W+Mo content, when the amount of Re added increases by 0.5wt%, the amount of W+Mo added decreases by 0.8-1.2wt% accordingly. (2) The C content is positively correlated with the sum of Hf+Ti+Nb content. Within the range of the sum of C content and Hf+Ti+Nb content, when the amount of C added increases by 0.03wt%, the amount of Hf+Ti+Nb added increases by 0.4-0.6wt%.
2. The high-purity, high-stability nickel-based single-crystal superalloy according to claim 1, characterized in that, The mass percentage of the impurity elements is controlled as follows: S≤0.0002wt%, O≤0.0004wt%, N≤0.0002wt%. The Mg content is positively correlated with the Hf content. Within the range of Mg and Hf content, when the amount of Hf added increases by 0.05wt%, the amount of Mg added increases by 0.001-0.0015wt%.
3. A method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 1 or 2, characterized in that, The preparation method includes the following steps in sequence: Step 1: Place all Cr raw materials and part of Ni raw materials into an electron beam melting furnace, and melt and purify them according to the preset process parameters to obtain NiCr master alloy. Step 2: After evacuating the vacuum induction melting furnace to the preset vacuum level, add raw materials to the ceramic crucible inside the furnace in the following order: First, spread the preset proportion of C raw material evenly at the bottom of the ceramic crucible as the bottom raw material layer; then mix the remaining Ni raw material, all NiCr master alloy and all Co raw material evenly and spread them evenly on the bottom raw material layer as the middle raw material layer; finally, mix all Re raw material, all W raw material, all Mo raw material and all Nb raw material evenly and spread them evenly on the middle raw material layer as the upper raw material layer. Step 3: Heat the furnace charge according to the preset power. After the charge has completely melted and formed a molten pool, raise the temperature of the alloy melt to the refining temperature and refine it. After refining, cool the alloy melt back to the preset temperature. Step 4: Slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Ti raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt. Step 5: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, and then add all the Al raw materials to the alloy melt. After the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float to the surface of the alloy melt. Then, immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step Six: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the preset proportion of C raw material to the alloy melt, and then add all of the Ce raw material to the alloy melt. After the feeding is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to fully float to the surface of the alloy melt. Step 7: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The feeding sequence is as follows: first, add the C raw material in the preset proportion to the alloy melt, then mix all the Y raw materials and all the La raw materials evenly and add them to the alloy melt; after the feeding is completed, continue electromagnetic stirring for the preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 8: Continue to slowly add raw materials to the alloy melt while electromagnetically stirring. The order of adding materials is as follows: first, mix all Hf raw materials and all B raw materials evenly and then add them to the alloy melt, then add all Mg raw materials to the alloy melt; after the addition is completed, continue electromagnetic stirring for a preset time to allow the inclusions in the alloy melt to float fully to the surface of the alloy melt, and then immerse a porous ceramic plate on the surface of the alloy melt to adsorb the inclusions. Step 9: Adjust the temperature of the alloy melt to the pouring temperature and pour it. During the pouring process, multi-stage filtration is used to obtain a high-purity master alloy ingot. The master alloy ingot is remelted and directionally solidified using the spiral crystal selection method or seed crystal method to obtain a single crystal casting. The single crystal casting is subjected to solution treatment and aging treatment to finally obtain a high-purity and high-stability nickel-based single crystal high-temperature alloy casting.
4. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 3, characterized in that, In step one, the Ni raw material added to the electron beam melting furnace accounts for 70-90 wt% of the total mass of the Ni raw material, and both the Cr and Ni raw materials are added in elemental form. The preset process parameters include: molten pool temperature 1650-1800℃, vacuum degree less than or equal to 0.1Pa, and scanning speed 10-30mm / min.
5. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 4, characterized in that, In step two, the vacuum degree of the vacuum induction melting furnace is less than or equal to 1 Pa; the added C raw material accounts for 30-35 wt% of the total mass of C raw material, and C, Ni, Co, Re, W, Mo and Nb raw materials are all added in elemental form; In step three, the preset power is 600-800kW, the refining temperature is 1560-1600℃, the refining time is 30-90min, and after refining, the alloy melt is cooled to 1430-1470℃.
6. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 5, characterized in that, In step four, the added C raw material accounts for 5-6 wt% of the total mass of C raw material. Both C and Ti raw materials are added in elemental form. After the feeding is completed, continue electromagnetic stirring for 3-10 minutes. In step five, the amount of raw material C added is five times that added in step four. Both raw material C and raw material Al are added in elemental form. After the feeding is completed, continue electromagnetic stirring for 3-10 minutes.
7. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 6, characterized in that, In step six, the added C raw material accounts for 10-12 wt% of the total mass of C raw material. The C raw material is added in elemental form, and the Ce raw material is added in the form of NiCe master alloy. After the feeding is completed, continue electromagnetic stirring for 3-10 minutes. In step seven, the amount of C material added is twice that added in step six. The C material is added in elemental form, while the Y material and La material are added in the form of NiY master alloy and NiLa master alloy, respectively. After the feeding is completed, continue electromagnetic stirring for 3-10 minutes. In step eight, Hf and B raw materials are added in elemental form, and Mg raw material is added in NiMg master alloy form. After the feeding is completed, electromagnetic stirring continues for 3-10 minutes.
8. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 7, characterized in that, In steps five, seven, and eight, the thickness of the porous ceramic plate is 20-30 mm, and its diameter is 0.7-0.9 times the inner diameter of the ceramic crucible; the porous ceramic plate has a multi-layer irregular pore structure with a pore density of not less than 10 PPI; the material of the porous ceramic plate is any one of zirconium oxide, alumina, or yttrium oxide. The porous ceramic plate needs to be baked before use. The baking temperature is 1000-1100℃ and the baking time is 4-8 hours. The porous ceramic plate is immersed in the surface of the alloy melt to adsorb inclusions for 3-5 seconds, and then the porous ceramic plate is slowly removed.
9. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 8, characterized in that, In step nine, at least three levels of filter screens are sequentially and spaced apart inside the trough-shaped gating channel along the flow direction of the alloy liquid, namely the first level filter screen, the second level filter screen, ..., the N-1th level filter screen and the Nth level filter screen. Each level of filter screen has a multi-layer irregular pore structure and is made of ceramic-based material. The pore density of each filter screen must meet the following conditions: the pore density of the first-stage filter screen is the lowest, not less than 10 PPI; the pore density of the (N-1)th-stage filter screen is the highest, not less than 30 PPI; except for the first-stage filter screen and the (N-1)th-stage filter screen, the pore density of the remaining filter screens increases sequentially along the flow direction of the alloy liquid.
10. The method for preparing a high-purity, high-stability nickel-based single-crystal superalloy according to claim 9, characterized in that, In step nine, during the preparation stage of the master alloy ingot, the casting temperature is 1480-1540℃; during the directional solidification stage, the refining temperature is 1600-1640℃, the upper heater temperature is 1500-1540℃, the lower heater temperature is 1520-1560℃, the casting temperature is 1520-1560℃, and the pulling rate after casting is 2-5mm / min. Solution treatment regime: First, perform solution treatment at 1180-1200℃ for 1-3 hours, then raise the temperature to 1250-1270℃ at a rate not exceeding 5℃ / min for 2-6 hours of solution treatment, and then air cool to room temperature; Aging treatment process: First, perform high-temperature aging treatment at 1070-1100℃ for 1-3 hours, followed by air cooling to room temperature; then, perform low-temperature aging treatment at 850-880℃ for 18-32 hours, followed by air cooling to room temperature.
Citation Information
Patent Citations
Preparation method of nickel-based single-crystal high-temperature alloy with high structure stability and high Re content
CN118957361A
Fifth-generation nickel-based single-crystal high-temperature alloy with high-stability structure
CN119553140A